Melanie Klein and beyond : a bibliography of primary and secondary sources - Karnac, Harry (Karnac, 2009)
'Did Melanie Klein ever think that 50 years after her death her ideas would be spreading world-wide in such a fruitful and productive way? In one sense she would be surprised, but in another, I think she might have regarded it as just to be expected. She had a very high regard for her own work, and enormous confidence that she was on to something new. At the same time she was fatefully resigned to being misunderstood and rejected - just as Freud had been, of course. But now, here is the evidence of her success: two thousand plus references, and climbing. Klein's ideas are truly international n.